Asphalt pavement anti-rutting modifier and preparation method and application thereof
By growing carbon nanotubes in situ on the surface of basalt fibers and blending them with organic wax warm mixer, an anti-rut modifier on asphalt pavement was prepared, which solved the problem of asphalt smoke and low-temperature cracking in existing asphalt pavements under high temperature conditions. Improve the high and low temperature properties of asphalt composites and reduce production costs.
Patent Information
- Application Number
- CN202411474503.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing asphalt pavement will produce a large amount of asphalt smoke when constructed under high temperature conditions, and it is prone to cracking in low temperature environments, affecting the service life of the pavement. At the same time, the preparation process of existing modifiers is complicated and costly, and the compatibility between polymer modifiers and asphalt is poor, making segregation phenomenon prone to occur.
Carbon nanotube-loaded basalt fiber hybrids are used as modifiers to grow carbon nanotubes in situ on the surface of basalt fibers through catalyst cracking reaction, and blend them with organic wax warm mixer, dispersant and antioxidant to prepare asphalt pavement Anti-rut modifier.
Improve the high-temperature rutting resistance and permanent deformation resistance of modified asphalt composites, reduce the emission of asphalt smoke, improve the interface compatibility between asphalt and basalt fibers, reduce production costs, and realize the waste plastics High value added transformation.
Smart Images

Figure CN118978810B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer composite materials, in particular to an anti-rutting modifier for asphalt pavement and a preparation method and application thereof. Background Art
[0002] Hot mix asphalt (HMA) is used in traditional asphalt road construction, which can build a road surface with stable performance. However, it needs to be constructed under high temperature conditions (around 180°C). During the mixing and paving process of the asphalt mixture, a large amount of asphalt smoke will be generated, which contains a variety of gas components that are harmful to the human body and the environment.
[0003] At present, the main approach is to add materials with large specific surface area and porous structure to asphalt, such as graphite, nano calcium carbonate, etc., to absorb the light components of asphalt and reduce the free asphalt to achieve the purpose of suppressing asphalt fume emissions. Carbon nanotubes are expected to be used to modify asphalt and reduce asphalt fume emissions due to their rich pore structure and large specific surface area.
[0004] Low-temperature cracking is one of the main ways of asphalt pavement failure in my country. In low-temperature environments, once the pavement cracks, the traffic load will cause the cracks to expand rapidly, seriously affecting the service life of the pavement. Therefore, the study of the low-temperature performance of carbon nanotube-modified asphalt mixtures is of great significance for preventing and controlling low-temperature cracking of pavements. Compared with general modified materials, carbon nanotubes, as nano-scale modified materials, have excellent electrothermal and mechanical properties. They can change the structural properties of asphalt mixtures at the nanoscale and significantly improve the tensile and compressive strength and high-temperature rheological properties of asphalt concrete.
[0005] 1. The invention patent with application number CN201410003251.5 discloses an asphalt modifier and its preparation method, specifically, 20%-30% polyethylene resin, 30%-50% palmitic acid, and 30%-50% hard amide are uniformly mixed in proportion and added to the asphalt composite material to prepare a low-temperature toughened asphalt composite material. Although this method prepares a low-temperature asphalt modifier, the method is complicated to prepare and has high cost, and is not suitable for large-scale application;
[0006] 2. The invention patent with application number CN201210308400.X discloses an epoxidized SBS modified asphalt and its production process. Specifically, the preparation of styrene-butadiene-styrene block copolymer (SBS) can improve the high-temperature stability of asphalt and improve the asphalt's resistance to low-temperature cracking. However, most polymer modifiers have poor compatibility with asphalt and are prone to segregation when added to asphalt, affecting the modification effect of the polymer.
[0007] Therefore, how to ensure the adsorption of toxic gases from the cracking of high-temperature heated asphalt, reduce the viscosity of asphalt composites while meeting their required mechanical properties and low-temperature properties, and have a simple preparation process, is of great significance for the high-value utilization of waste polyolefins. Summary of the invention
[0008] The object of the present invention is to provide an anti-rutting modifier for asphalt pavement to solve the problems raised in the above background technology.
[0009] In the first aspect, to achieve the above-mentioned purpose, the present invention provides the following technical solutions: an anti-rutting modifier for asphalt pavement, comprising the following raw materials in parts by weight: 100 parts of carbon nanotube-loaded basalt fiber hybrid, 20-50 parts of organic wax warm mix, 0.5-1 part of dispersant, and 0.5-1 part of antioxidant;
[0010] The preparation method of the carbon nanotube-loaded basalt fiber hybrid is as follows:
[0011] Step 1: Degumming of basalt fiber: Put the basalt fiber into a heating furnace, heat it to 300℃, keep it warm for 1h, and remove the surface impregnation agent;
[0012] Step 2, preparation of catalyst-loaded basalt fiber: soak the degummed basalt fiber in the catalyst for 60 seconds, then transfer it to a 40°C oven for drying, repeat the soaking and drying three times, then transfer it to a 220°C constant temperature oven for treatment for 30 minutes, then take it out, wash it with water, and dry it at room temperature to obtain activated basalt fiber, immerse the activated basalt fiber in the plating solution for 1 hour, then put it into an oven at 75°C for cobalt plating, take it out after the time is up, wash it with water, and dry it to obtain catalyst-loaded basalt fiber;
[0013] Step 3, preparation of carbon nanotube-loaded basalt fiber hybrid: waste polyolefin and catalyst-loaded basalt fiber are placed in a heating furnace, and under the protection of protective gas, a catalyst cracking reaction is carried out, and then added to a flat vulcanizer, and hot-pressed at 180°C to obtain a carbon nanotube-loaded basalt fiber hybrid.
[0014] Wherein, the organic wax warm-mix agent is one or more combinations of plant wax, animal wax, cracked wax, petroleum wax and synthetic wax.
[0015] Wherein, the dispersant is one or more combinations of polyvinyl pyrrolidone, sodium lauryl sulfate, ammonium lauryl sulfate and polyethylene oxide.
[0016] Wherein, the antioxidant is one or more combinations of tea polyphenols, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, diphenyloctyl phosphite and triphenyl phosphate.
[0017] Wherein, in step 2, the catalyst is a mixed solution of cobalt nitrate and sodium hypophosphite, and the mass ratio of the cobalt nitrate and sodium hypophosphite is 1:1.
[0018] Wherein, in step three, the waste polyolefin is one or more combinations of polyethylene, polypropylene, polystyrene, rubber powder and ethylene-vinyl acetate copolymer.
[0019] Among them, in step three, the protective gas is one or a combination of nitrogen and argon, the introduction rate of the protective gas is 0.5-1.5L / min, and the introduction direction of the protective gas starts from room temperature until the heating temperature of the heating furnace reaches 400°C, and then the introduction is stopped.
[0020] Among them, in step three, the mass ratio of catalyst-loaded basalt fiber to waste polyolefin is: 1:5-25, the temperature of the catalyst cracking reaction is 700-900°C, the time of the catalyst cracking reaction is 3-6h, and the heating rate of the heating furnace is 5-10°C / min.
[0021] In a second aspect, the present invention provides a method for preparing the above-mentioned asphalt pavement anti-rutting modifier, comprising the following steps:
[0022] Adding the carbon nanotube-loaded basalt fiber hybrid, an organic wax warming agent, a dispersant, and an antioxidant into a twin-screw extruder;
[0023] After blending and granulation, an asphalt pavement anti-rutting modifier is obtained;
[0024] Among them, the barrel temperature of the twin-screw extruder is 150-200°C, the main engine speed is 400-700r / min, and the feeding frequency is 5-8r / min.
[0025] In a third aspect, the present invention provides a use of the above-mentioned asphalt pavement anti-rutting modifier in asphalt.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention first loads a catalyst on the surface of degummed basalt fiber; then, high molecular weight waste plastic is catalytically cracked to prepare low-cost carbon nanotubes, wherein the carbon nanotubes are obtained by in-situ growth on the surface of basalt fiber using waste plastic as a carbon source through catalytic cracking of the catalyst; the obtained carbon nanotubes are loaded on the basalt fiber, thereby improving the high-temperature rutting resistance and permanent deformation resistance of the modified asphalt composite material; the basalt fiber in the asphalt pavement anti-rutting modifier provided by the present invention has a high specific surface area and has a high-temperature resistance effect on asphalt, and the interconnection between the carbon nanotubes can construct a three-dimensional network in the asphalt, thereby improving the interface compatibility between the basalt fiber and the asphalt matrix, thereby improving the high-temperature rutting resistance and permanent deformation resistance of the modified asphalt composite material.
[0028] 2. The organic wax-based warm mix agent in the present invention has the effect of reducing the viscosity of asphalt and can help disperse basalt fiber-carbon nanotubes in asphalt; at the same time, the asphalt pavement anti-rutting modifier of the present invention can improve the stability and durability of asphalt, and make up for the defects of poor low-temperature performance of modified asphalt composite materials. The addition of the asphalt pavement anti-rutting modifier makes the base asphalt have good mechanical properties and pavement performance.
[0029] 3. The waste polyolefin in the asphalt pavement anti-rutting modifier of the present invention is derived from waste plastics, which realizes high value-added transformation of waste plastics, is beneficial to reducing white pollution, achieves energy conservation and environmental protection, and greatly reduces production costs.
[0030] 4. The carbon nanotubes in the present invention have rich pore structures and large specific surface area, and can be used to modify asphalt and reduce the emission of asphalt smoke. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The present invention is a flow chart of the method for preparing carbon nanotubes by plating catalyst and cracking and growing carbon nanotubes;
[0032] Figure 2 This is a SEM image of basalt fiber loaded with carbon nanotubes prepared in Example 1;
[0033] Figure 3 This is a SEM image of basalt fiber loaded with carbon nanotubes prepared in Example 2;
[0034] Figure 4 This is a SEM image of basalt fiber loaded with carbon nanotubes prepared in Example 3;
[0035] Figure 5 This is a TEM image of basalt fiber loaded with carbon nanotubes prepared in Example 1;
[0036] Figure 6 It is a data diagram of the high temperature performance phase angle of the asphalt composite material of Examples 1, 4-6 and Comparative Example 1;
[0037] Figure 7 It is a data diagram of the low temperature performance phase angle of the asphalt composite material of Examples 1, 4-6 and Comparative Example 1;
[0038] Figure 8 It is a data graph of high temperature performance complex shear modulus of the asphalt composite material of Examples 1, 4-6 and Comparative Example 1;
[0039] Fig. 9 It is a data graph of the low temperature performance complex shear modulus of the asphalt composite material of Examples 1, 4-6 and Comparative Example 1;
[0040] Fig.10 It is a data graph of the high temperature performance rutting factor of the asphalt composite material of Examples 1, 4-6 and Comparative Example 1;
[0041] Fig.11 It is a data graph of the low temperature performance rutting factor of the asphalt composite materials of Examples 1, 4-6 and Comparative Example 1. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Example 1
[0043] See also Figure 1-Figure 11 This embodiment provides a technical solution: a method for preparing an asphalt pavement anti-rutting modifier, comprising the following steps:
[0044] Step 1: Degumming of basalt fiber: Put the basalt fiber into a heating furnace, heat it to 300℃ and calcine it, keep it warm for 1 hour, and remove the surface impregnation agent;
[0045] Step 2, preparation of catalyst-loaded basalt fiber: 35g of cobalt nitrate and 35g of sodium hypophosphite are prepared into 500mL of catalyst, then 50g of the above-mentioned degummed basalt fiber is weighed, the degummed basalt fiber is immersed in the catalyst for 60s, then transferred to a 40°C oven for drying, the immersion and drying are repeated three times, then transferred to a 220°C constant temperature oven for treatment for 30min, then taken out for washing, and dried at room temperature to obtain activated basalt fiber, the activated basalt fiber is immersed in a plating solution (the plating solution is a mixture of 15g of cobalt nitrate, 7.5g of sodium hypophosphite, 7.5g of sodium succinate, and 0.18g of succinic acid) for 1h, then placed in an oven at 75°C for cobalt plating, taken out after the time is up, washed with water, and dried to obtain a catalyst-loaded basalt fiber;
[0046] Step 3, preparation of carbon nanotube-loaded basalt fiber hybrid: Then weigh 0.9g of catalyst-loaded basalt fiber and 3.6g of waste high-density polyethylene (HDPE), put the waste high-density polyethylene (HDPE) and the catalyst-loaded basalt fiber into a heating furnace, and carry out a catalyst cracking reaction (the temperature of the catalyst cracking reaction is 700-900°C, the time of the catalyst cracking reaction is 3-6h, and the heating rate of the heating furnace is 5-10°C / min) under the protection of protective gas (the protective gas is one or a combination of nitrogen and argon, the introduction rate of the protective gas is 0.5-1.5L / min, and the introduction direction of the protective gas starts from room temperature until the heating temperature of the heating furnace reaches 400°C, and the introduction is stopped), and then add them into a flat vulcanizer, and perform hot pressing molding at 180°C to obtain a carbon nanotube-loaded basalt fiber hybrid;
[0047] Step 4: Add 100 parts of carbon nanotube-loaded basalt fiber hybrid, 35 parts of organic wax warm mix, 1 part of dispersant and 1 part of antioxidant into a twin-screw extruder; after blending and granulation, obtain an asphalt pavement anti-rutting modifier (basalt fiber loaded carbon nanotubes), such as Figure 2 and Figure 5 As shown by Figure 2 We can see very obvious carbon nanotubes and basalt fiber layered structures. Carbon nanotubes grow out from the fiber gaps. (a) and (b) correspond to different magnifications. Figure 5 The carbon nanotubes on the basalt fiber can be clearly seen, where (a) and (b) correspond to different magnifications; the barrel temperature of the twin-screw extruder is 150-200°C, the main engine speed is 400-700r / min, and the feeding frequency is 5-8r / min.
[0048] The asphalt pavement anti-rutting modifier is applied in asphalt, specifically: weigh 4 parts of the above-mentioned asphalt pavement anti-rutting modifier and 100 parts of 70# asphalt, heat to 145°C, wait until the asphalt is completely melted, use a high-speed shearing machine to shear, the shearing machine speed is 3000 rpm, the shearing time is 30 min, after the shearing is completed, pour it into a silicone mold while hot to obtain a basalt fiber-loaded carbon nanotube-modified asphalt composite material. Example 2
[0049] See also Figure 1-Figure 11 This embodiment provides a technical solution: a method for preparing an asphalt pavement anti-rutting modifier, comprising the following steps:
[0050] Step 1: Degumming of basalt fiber: Put the basalt fiber into a heating furnace, heat it to 300℃ and calcine it, keep it warm for 1 hour, and remove the surface impregnation agent;
[0051] Step 2, preparation of catalyst-loaded basalt fiber: 35g of cobalt nitrate and 35g of sodium hypophosphite are prepared into 500mL of catalyst, then 50g of the above-mentioned degummed basalt fiber is weighed, the degummed basalt fiber is immersed in the catalyst for 60s, then transferred to a 40°C oven for drying, the immersion and drying are repeated three times, then transferred to a 220°C constant temperature oven for treatment for 30min, then taken out for washing, and dried at room temperature to obtain activated basalt fiber, the activated basalt fiber is immersed in a plating solution (the plating solution is a mixture of 15g of cobalt nitrate, 7.5g of sodium hypophosphite, 7.5g of sodium succinate, and 0.18g of succinic acid) for 1h, then placed in an oven at 75°C for cobalt plating, taken out after the time is up, washed with water, and dried to obtain a catalyst-loaded basalt fiber;
[0052] Step 3, preparation of carbon nanotube-loaded basalt fiber hybrid: Then weigh 0.9g of catalyst-loaded basalt fiber and 3.6g of waste polypropylene (PP), put the waste polypropylene (PP) and the catalyst-loaded basalt fiber into a heating furnace, and carry out a catalyst cracking reaction (the temperature of the catalyst cracking reaction is 700-900°C, the time of the catalyst cracking reaction is 3-6h, and the heating rate of the heating furnace is 5-10°C / min) under the protection of protective gas (the protective gas is one or a combination of nitrogen and argon, the introduction rate of the protective gas is 0.5-1.5L / min, and the introduction direction of the protective gas starts from room temperature until the heating temperature of the heating furnace reaches 400°C, and the introduction is stopped), and then add them into a flat vulcanizer, and perform hot pressing molding at 180°C to obtain a carbon nanotube-loaded basalt fiber hybrid;
[0053] Step 4: Add 100 parts of carbon nanotube-loaded basalt fiber hybrid, 35 parts of organic wax warm mix, 1 part of dispersant and 1 part of antioxidant into a twin-screw extruder; after blending and granulation, obtain an asphalt pavement anti-rutting modifier (basalt fiber loaded carbon nanotubes), such as Figure 3 As shown by Figure 3 It can be seen that the carbon nanotubes and basalt fiber layered structures are very obvious, and the carbon nanotubes grow out through the fiber gaps, where (a) and (b) correspond to different magnifications; the barrel temperature of the twin-screw extruder is 150-200℃, the main engine speed is 400-700r / min, and the feeding frequency is 5-8r / min.
[0054] The asphalt pavement anti-rutting modifier is applied in asphalt, specifically: weigh 4 parts of the above-mentioned asphalt pavement anti-rutting modifier and 100 parts of 70# asphalt, heat to 145°C, wait until the asphalt is completely melted, use a high-speed shearing machine to shear, the shearing machine speed is 3000 rpm, the shearing time is 30 min, after the shearing is completed, pour it into a silicone mold while hot to obtain a basalt fiber-loaded carbon nanotube-modified asphalt composite material. Example 3
[0055] See also Figure 1-Figure 11 This embodiment provides a technical solution: a method for preparing an asphalt pavement anti-rutting modifier, comprising the following steps:
[0056] Step 1: Degumming of basalt fiber: Put the basalt fiber into a heating furnace, heat it to 300℃ and calcine it, keep it warm for 1 hour, and remove the surface impregnation agent;
[0057] Step 2, preparation of catalyst-loaded basalt fiber: 35g of cobalt nitrate and 35g of sodium hypophosphite are prepared into 500mL of catalyst, then 50g of the above-mentioned degummed basalt fiber is weighed, the degummed basalt fiber is immersed in the catalyst for 60s, then transferred to a 40°C oven for drying, the immersion and drying are repeated three times, then transferred to a 220°C constant temperature oven for treatment for 30min, then taken out for washing, and dried at room temperature to obtain activated basalt fiber, the activated basalt fiber is immersed in a plating solution (the plating solution is a mixture of 15g of cobalt nitrate, 7.5g of sodium hypophosphite, 7.5g of sodium succinate, and 0.18g of succinic acid) for 1h, then placed in an oven at 75°C for cobalt plating, taken out after the time is up, washed with water, and dried to obtain a catalyst-loaded basalt fiber;
[0058] Step 3, preparation of carbon nanotube-loaded basalt fiber hybrid: Then weigh 0.9g of catalyst-loaded basalt fiber and 3.6g of waste high-density polystyrene (PS), put the waste high-density polystyrene (PS) and the catalyst-loaded basalt fiber into a heating furnace, and carry out a catalyst cracking reaction (the temperature of the catalyst cracking reaction is 700-900°C, the time of the catalyst cracking reaction is 3-6h, and the heating rate of the heating furnace is 5-10°C / min) under the protection of protective gas (the protective gas is one or a combination of nitrogen and argon, the introduction rate of the protective gas is 0.5-1.5L / min, and the introduction direction of the protective gas starts from room temperature until the heating temperature of the heating furnace reaches 400°C, and the introduction is stopped), and then add them into a flat vulcanizer, and perform hot pressing molding at 180°C to obtain a carbon nanotube-loaded basalt fiber hybrid;
[0059] Step 4: Add 100 parts of carbon nanotube-loaded basalt fiber hybrid, 35 parts of organic wax warm mix, 1 part of dispersant and 1 part of antioxidant into a twin-screw extruder; after blending and granulation, obtain an asphalt pavement anti-rutting modifier (basalt fiber loaded carbon nanotubes), such as Figure 4 As shown by Figure 4It can be seen that the carbon nanotubes and basalt fiber layered structures are very obvious, and the carbon nanotubes grow out through the fiber gaps, where (a) and (b) correspond to different magnifications; the barrel temperature of the twin-screw extruder is 150-200℃, the main engine speed is 400-700r / min, and the feeding frequency is 5-8r / min.
[0060] The asphalt pavement anti-rutting modifier is applied in asphalt, specifically: weigh 4 parts of the above-mentioned asphalt pavement anti-rutting modifier and 100 parts of 70# asphalt, heat to 145°C, wait until the asphalt is completely melted, use a high-speed shearing machine to shear, the shearing machine speed is 3000 rpm, the shearing time is 30 min, after the shearing is completed, pour it into a silicone mold while hot to obtain a basalt fiber-loaded carbon nanotube-modified asphalt composite material. Example 4
[0061] The difference between this embodiment and embodiment 1 is that when the asphalt pavement anti-rutting modifier is applied to asphalt, 1 part of the asphalt pavement anti-rutting modifier is weighed. Example 5
[0062] The difference between this embodiment and embodiment 1 is that when the asphalt pavement anti-rutting modifier is applied to asphalt, 2 parts of the asphalt pavement anti-rutting modifier are weighed. Example 6
[0063] The difference between this embodiment and embodiment 1 is that when the asphalt pavement anti-rutting modifier is applied to asphalt, 3 parts of the asphalt pavement anti-rutting modifier are weighed.
[0064] Comparative Example 1
[0065] Weigh 100 parts of 70# asphalt, heat it to 145°C, and then use a high-speed shearing machine to shear at a shear rate of 3000rpm and a shearing time of 30 min. After the shearing is completed, pour it into a silicone mold while it is hot to obtain the asphalt material.
[0066] Comparative Example 2
[0067] Weigh 0.1g of basalt fiber coated with cobalt nitrate catalyst and 10g of polyethylene, mix the two evenly, and then add them into a flat vulcanizer for hot pressing at a heating temperature of 180°C. After the hot pressing reaches the point where the polyethylene melts, the material can be removed to obtain a composite material of waste polyolefin and cobalt nitrate;
[0068] Waste polyolefin and cobalt nitrate complex / wax-based warming agent were added to a ceramic boat, and then the ceramic boat was placed in a tube furnace, nitrogen was introduced for 10 minutes, and the air in the tube furnace was exhausted. The boat was heated to 900°C at a heating rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 6 hours. The tube furnace was cooled to room temperature, and the obtained black powder solid was taken out to obtain carbon nanotubes.
[0069] Weigh 1.5 parts of carbon nanotube-basalt fiber / wax-based warm mix agent composite modified material and 100 parts of 70# asphalt, mix the two evenly, heat to 145°C, wait until the asphalt is completely melted, and use a high-speed shearing machine to shear at a speed of 3000 rpm and a shearing time of 30 min. After shearing, pour it into a silicone mold while hot to obtain a warm mix asphalt composite material.
[0070] Comparative Example 3
[0071] Weigh 3 parts of cobalt-coated basalt fiber and 100 parts of 70# asphalt, mix the two evenly, heat to 145°C, wait until the asphalt is completely melted, and use a high-speed shearing machine to shear at a speed of 3000 rpm and a shearing time of 30 minutes. After shearing, pour it into a silicone mold while hot to obtain a warm-mix asphalt composite material.
[0072] Comparative Example 4
[0073] Weigh 3 parts of carbon nanotubes and 100 parts of 70# asphalt, mix the two evenly, heat to 145°C, wait until the asphalt is completely melted, and use a high-speed shearing machine to shear at a speed of 3000 rpm and a shearing time of 30 min. After shearing, pour it into a silicone mold while hot to obtain a warm-mix asphalt composite material.
[0074] Experimental example
[0075] Performance testing;
[0076] According to the AASHTO T 315-02 standard, the high temperature performance and low temperature performance of the asphalt composite materials of Examples 1-6 and Comparative Examples 1-4 were tested using the MCR702 advanced rheometer produced by Anton Paar GmbH of Austria. The results are as follows: Figure 6-11 shown.
[0077] Depend on Figure 6 It can be seen that the phase angle of the modified asphalt material with the addition of asphalt pavement anti-rutting modifier (basalt fiber loaded with carbon nanotubes) is reduced, indicating that the carbon nanotubes have a good viscosity reduction effect; Figure 8 and 10 It can be seen that the high-temperature complex shear modulus and high-temperature rutting factor of the asphalt composite material modified by the asphalt pavement anti-rutting modifier (basalt fiber loaded with carbon nanotubes) are greater than those of the comparative example 1, indicating that its high-temperature performance is better than that of the comparative example 1; Figure 7 It can be seen that the phase angle of the asphalt composite material after adding the asphalt pavement anti-rutting modifier (basalt fiber loaded with carbon nanotubes) is not significantly reduced, and the fusion condition is still good at low temperature; Fig. 9 and 11It can be seen that the low-temperature shear and rutting factors of the asphalt composite material using the asphalt pavement anti-rutting modifier (basalt fiber loaded with carbon nanotubes) are generally greater than those of Comparative Example 1, indicating that its low-temperature performance is better than the low-temperature performance of Comparative Example 1; overall, the high-temperature performance is mainly improved. When the added content of the asphalt pavement anti-rutting modifier (basalt fiber loaded with carbon nanotubes) is 3 parts, the high-temperature performance of the composite asphalt material is most significantly improved; when the content of the asphalt pavement anti-rutting modifier (basalt fiber loaded with carbon nanotubes) is 2-3 parts, the low-temperature performance of the composite asphalt material is significantly improved.
[0078] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
Claims
1. An anti-rutting modifier for asphalt pavement, characterized in that: The invention is composed of the following raw materials in parts by weight: 100 parts of carbon nanotube-loaded basalt fiber hybrid, 20-50 parts of organic wax warm-mix agent, 0.5-1 part of dispersant, and 0.5-1 part of antioxidant; The preparation method of the carbon nanotube-loaded basalt fiber hybrid is as follows: Step 1: Degumming of basalt fiber: Put the basalt fiber into a heating furnace, heat it to 300℃, keep it warm for 1h, and remove the surface impregnation agent; Step 2, preparation of catalyst-loaded basalt fiber: soak the degummed basalt fiber in a catalyst, wherein the catalyst is a mixed solution of cobalt nitrate and sodium hypophosphite, wherein the mass ratio of cobalt nitrate to sodium hypophosphite is 1:1, soak for 60 seconds, then transfer to a 40°C oven for drying, repeat the soaking and drying three times, then transfer to a 220°C constant temperature oven for treatment for 30 minutes, then take out, wash with water, and dry at room temperature to obtain activated basalt fiber, immerse the activated basalt fiber in a plating solution for 1 hour, then put it into an oven at 75°C for cobalt plating, take it out after the time is up, wash with water, and dry it to obtain catalyst-loaded basalt fiber; Step 3, preparation of carbon nanotube-loaded basalt fiber hybrid: waste polyolefin and catalyst-loaded basalt fiber are placed in a heating furnace, and under the protection of protective gas, a catalyst cracking reaction is carried out, and then added to a flat vulcanizer, and hot-pressed at 180°C to obtain a carbon nanotube-loaded basalt fiber hybrid.
2. The asphalt pavement anti-rutting modifier according to claim 1, characterized in that: The organic wax warm-mix agent is one or more combinations of plant wax, animal wax, cracked wax, petroleum wax and synthetic wax.
3. The asphalt pavement anti-rutting modifier according to claim 1, characterized in that: The dispersant is one or more combinations of polyvinyl pyrrolidone, sodium lauryl sulfate, ammonium lauryl sulfate and polyethylene oxide.
4. The asphalt pavement anti-rutting modifier according to claim 1, characterized in that: The antioxidant is one or more combinations of tea polyphenols, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, diphenyloctyl phosphite and triphenyl phosphate.
5. The asphalt pavement anti-rutting modifier according to claim 1, characterized in that: In step three, the waste polyolefin is one or more combinations of polyethylene, polypropylene, polystyrene, rubber powder and ethylene-vinyl acetate copolymer.
6. The asphalt pavement anti-rutting modifier according to claim 1, characterized in that: In step three, the protective gas is one or a combination of nitrogen and argon, the introduction rate of the protective gas is 0.5-1.5L / min, and the introduction direction of the protective gas starts from room temperature until the heating temperature of the heating furnace reaches 400°C, and then the introduction is stopped.
7. The asphalt pavement anti-rutting modifier according to claim 1, characterized in that: In step three, the mass ratio of catalyst-loaded basalt fiber to waste polyolefin is 1:5-25, the temperature of the catalyst cracking reaction is 700-900°C, the time of the catalyst cracking reaction is 3-6h, and the heating rate of the heating furnace is 5-10°C / min.
8. A method for preparing an asphalt pavement anti-rutting modifier suitable for use in any one of claims 1 to 7, characterized in that: The following steps are involved: Adding the carbon nanotube-loaded basalt fiber hybrid, an organic wax warming agent, a dispersant, and an antioxidant into a twin-screw extruder; After blending and granulation, an asphalt pavement anti-rutting modifier is obtained; Among them, the barrel temperature of the twin-screw extruder is 150-200°C, the main engine speed is 400-700r / min, and the feeding frequency is 5-8r / min.
9. Use of the asphalt pavement anti-rutting modifier according to any one of claims 1 to 7 in asphalt.
Citation Information
Patent Citations
Epoxidized SBS modified asphalt and its production process
CN102964850A
Asphalt modifier and preparation method thereof
CN103756340A
Graphene-basalt fiber enhanced copper based graphite motor carbon brush and preparation method thereof
CN106521367A
Anti-rutting recycled asphalt mixture and processing technology thereof
CN114573274A